Power System Controlled Islanding using Modified Discrete Optimization Techniques - Saharuddin N.Z.; Abidin I.Z.; Mokhlis H.; Hassan M.Y. (Science and Information Organization, 2023)
Computer programming; Distributed power generation; Electric lines; Electric power system control; Electric power transmission; Light transmission; Particle swarm optimization (PSO); Power control; Controlled islanding; Discrete particle swarm optimization; Evolutionary programming techniques; Minimal power; Minimal power flow disruption; Modified discrete evolutionary programming technique; Modified discrete particle swarm optimization technique; Particle swarm optimization technique; Power flows; Power imbalance; Electric load flow